Coordination Failure in Foreign Aid - Halonen-Akatwijuka, Maija (World Bank, Washington, D.C., 2013)
The author analyzes the allocation of foreign aid to various sectors in a recipient developing country. Donors tend to favor social sectors over other public expenditure programs. Due to incomplete information, donors may concentrate too much on priority sectors, leaving lower-priority yet important sectors lacking funds. Alternatively there may be gaps in services in priority areas because of the information problem. The author finds that the more similar preferences the donors have, the more scope there is for coordination failure. Therefore improving information is particularly important when the parties have similar priorities. A joint database on planned projects and budget allocations in each recipient country would provide such information. The author's point is that such databases should have both information on current projects and forward-looking information on the planned activities needed to improve aid coordination. She also analyzes the aid fungibility problem in an incomplete information setting and finds that incomplete information reduces the fungibility problem. On the other hand, incomplete information introduces coordination failure and the allocation can be inferior for both the recipient and the donor.